Selection Criteria of Public for Account Opening: A Case Study of Islamic Banks in Pakistan - Israr, Ahsan; Qureshi, Fahad Ahmed; Butt, Mubeen (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2018)
Banks have an immense role in deciding the economic fate of any state. The purpose of the study is to investigate the selection criteria of Islamic banking system for account opening. Data was collected and analysed through descriptive statistics, One Sample t test and Independent Sample t test. The results show that people prefer banks have the number of branches, wide range of products, low cost products, easily approachability. Results also shown, no significance difference in the selection criteria for Islamic banks among the customers based on Gender.DOI: 10.15408/aiq.v10i1.6011